The use of Diagnostic Imaging for Identifying Abnormal Gas Accumulations in Cetaceans and Pinnipeds - Dennison, Sophie; Fahlman, Andreas; Moore, Michael (Frontiers in Physiology, 2012)
Recent dogma suggested that marine mammals are not at risk of decompression sickness (DCS) due to a number of evolutionary adaptations. Several proposed adaptations exist. Lung compression and alveolar collapse that terminate gas exchange before a depth is reached where supersaturation is significant and bradycardia with peripheral vasoconstriction affecting the distribution, and dynamics of blood and tissue nitrogen levels. Published accounts of gas and fat emboli and dysbaric osteonecrosis in marine mammals and theoretical modeling have challenged this view-point, suggesting that decompression-like symptoms may occur under certain circumstances, contrary to common belief. Diagnostic imaging modalities are invaluable tools for the non-invasive examination of animals for evidence of gas and have been used to demonstrate the presence of incidental decompression-related renal gas accumulations in some stranded cetaceans. Diagnostic imaging has also contributed to the recognition of clinically significant gas accumulations in live and dead cetaceans and pinnipeds. Understanding the appropriate application and limitations of the available imaging modalities is important for accurate interpretation of results. The presence of gas may be incidental and must be interpreted cautiously alongside all other available data including clinical examination, clinical laboratory testing, gas analysis, necropsy examination and histology results.